POTENSI PENGGUNAAN MORTAR HIDROLIS SEBAGAI FILLER CELAH ANTAR SUSUNAN BATU CANDI SIWA PRAMBANAN - , Y. PAULUS H. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
On 27 May 2006 the temples at Prambanan temple complex were tested with the strength of the earthquake in Yogyakarta and surrounding areas. As a result of the quake buildings in the temple complex suffered severe damage including Shiva Temple. Custody due to interlocking between the rocks to resist lateral forces experienced by the Shiva temple building, the rocks making up the structure of the temple is to be broken or crac ked. Rocks making up the cause because the temple is not easy to shift due to its own weight and can also hit rock hit from the other rocks that can crack or rupture. Stone which can also occur due to an earthquake on the stone structure in the temple fell and hit another stone beneath it . Therefore, to fill the gap cracks rocks to do research on the mortar as a gap filler between the composition of the stone Shiva temple. This study aims to determine the compressive strength of mortar, the absorption of mortar, mortar shrinkage value, and the value of the viscosity of the hydraulic mortar mix as filler material making up rock fissures Shiva temple so we get the best mortar mix to be used as a gap filler material between the stone structure Shiva Temple. Research as a hydraulic mortar filler material Prambanan Shiva Temple is an experimental research conducted. This experimental study was done by finding the best mix of a few filler mortar mix. Of some of the existing mortar mix, then do trial and selection is based on the shape visually mortar and compressive strength results. Based on the results of the trial and selection of only the best mortar mix drawn were 8 different mix, then the compressive strength test, absorption of water, susutan mortar, and the viscosity of mortar mix. From the test results found that the compressive strength, absorbency, and is affected by the viscosity of hydraulic mortar mixture used water content and cement content contained in the mortar mix. The greater the water used in the mortar mix, it will reduce the compressive strength, increase the water absorption of mortar, and reduce the value of the coefficient of viscosity of the mortar mix. The addition of cement mortar will increase the compressive strength, reduces water absorption, and increase the value of the coefficient of viscosity. The best mortar mix design is mortar with sand ratio of 1.1: 1 lime: 1 red cement: 0.25 Pozolan portland cement with a water content of 0.55 is used for the total mixture of sand, lime, cement and portland cement Pozolan red. Compressive strength of 2.543 MPa, the value of 3.54 x 10-3 mPa.s viscosity (flow time 15.94 seconds), 12.7% water absorption, and mortar susutan value of 1.33%. When used 1 liter of a mixture of sand mortar required 212 ml, 193 ml lime, 193 ml of red cement, portland cement Pozolan 48 liter and 355 ml of water.